2010
DOI: 10.2478/v10102-010-0001-7
|View full text |Cite
|
Sign up to set email alerts
|

Protective effects of manganese(II) chloride on hyaluronan degradation by oxidative system ascorbate plus cupric chloride

Abstract: The degradation of several high-molar-mass hyaluronan samples was investigated in the presence of ascorbic acid itself and further by an oxidative system composed of ascorbic acid plus transition metal ions, i.e. Fe(II) or Cu(II) ions. The latter oxidative system imitates conditions in a joint synovial fluid during early phase of acute joint inflammation and can be used as a model for monitoring oxidative degradation of hyaluronan under pathophysiological conditions. The system Cu(II) plus ascorbate (the Weiss… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 56 publications
0
7
0
Order By: Relevance
“…However, at low doses manganese, differently from transition metals such as iron and copper, was found to act as a potent antioxidant in the protection against oxidative stress (Sziraki et al ., 1995). In vitro experiments revealed the ability of Mn(II) to scavenge oxygen free radicals generated in differently mediated lipid peroxidation conditions (Cavallini et al ., 1983 ; Coassin et al ., 1992 ; Sziráki et al ., 1999 ; Hussain & Ali, 1999 ; Valachová et al ., 2010 ).…”
Section: Introductionmentioning
confidence: 99%
“…However, at low doses manganese, differently from transition metals such as iron and copper, was found to act as a potent antioxidant in the protection against oxidative stress (Sziraki et al ., 1995). In vitro experiments revealed the ability of Mn(II) to scavenge oxygen free radicals generated in differently mediated lipid peroxidation conditions (Cavallini et al ., 1983 ; Coassin et al ., 1992 ; Sziráki et al ., 1999 ; Hussain & Ali, 1999 ; Valachová et al ., 2010 ).…”
Section: Introductionmentioning
confidence: 99%
“…As Figure 6 demonstrates, in contrast to the system investigated by Cheton and Archibald [ 12 ] and by Valachova et.al. [ 11 ], manganese brought about a higher gluconate degradation rate than copper and iron. Within 100 h of reaction, gluconates that had been degraded by manganese, copper, and iron were ca 20%, 9%, and 7% respectively.…”
Section: Resultsmentioning
confidence: 99%
“…Valachova et al. reported that the addition of manganese inhibited the degradation of hyaluronan samples by the ascorbic Fenton catalyzed by iron or copper [ 11 ]. The inhibition has been attributed to the ability of manganese (II) to act as hydroxyl free radicals scavenger.…”
Section: Introductionmentioning
confidence: 99%
“…First, redox reaction between the Mn(II) and Mn(III) states in C-Mn 3 O 4 NPs due to ligand to metal charge transfer may help it to act as a scavenger of hydroxyl and superoxide radicals (details are discussed in previous section of the text). Second, it may act as a chain-breaker in inhibiting iron-induced lipid peroxidation chain reactions [59,60], and as proposed in other studies, Mn(II) may scavenge peroxyl lipid radicals via the following reaction [61,62]: …”
Section: Resultsmentioning
confidence: 99%